ANALYSIS OF THE EFFECT OF TWO-DIMENSIONAL FOOD MODEL EDUCATIONAL MEDIA ON CHANGES IN STUDENTS’ KNOWLEDGE ABOUT SUGAR CONSUMPTION - Br. Siregar, Santy Anjelyna; Nurpratama, Widya Lestari (Jurnal Mitra Kesehatan, 2025)
Introduction: Adolescents were recorded to consume more than 50 grams of sugar per day, higher than the adult group, which had an average of 39.1 grams. This condition indicates the need for nutritional education interventions in schools to form healthier consumption habits. The use of two-dimensional food models can help students understand the portions and sugar content in various food products more effectively. The purpose of this study was to analyze the effect of two-dimensional food model educational media on students' knowledge of sugar consumption. Methods: This study employed a quasi-experimental approach with a single-group pre-test and post-test design. The study sample consisted of 94 respondents selected through purposive sampling. Data collection on knowledge was conducted using pre-test and post-test questionnaires containing 15 questions, which were then analyzed using the Wilcoxon Signed Rank Test. The educational media given to the subjects was a two-dimensional food model consisting of pictures of various sweet food and beverage products accompanied by nutritional information and illustrations of sugar measurements in teaspoons. The images were printed on HVS paper and mounted on cardboard to make them more sturdy. Results: The results showed that the average knowledge score increased from 64.91 points in the pre-test to 94.01 points in the post-test, with the percentage of good knowledge increasing from 7.4% to 95.7%. The Wilcoxon Signed Rank Test on the knowledge variable produced a significance value (2-tailed) of 0.000. Conclusion: Two-dimensional food model educational media significantly influence students' knowledge about sugar consumption. Future research should conduct the latest research related to foods or beverages that will be trending in the future as material for two-dimensional food model media.